Hypnoteaching Method for Developing Students' Humility Attitude in Islamic Education Learning - Hamida, Wanda; Maknin, Nur Afifah Khurin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2024)
Islamic education primarily aims to instil moral values in students, with tawadhu' being a key emphasized aspect, representing humility and respect in interpersonal interactions. However, in practice, many students struggle to embody the virtue of tawadhu'. This research aims to bridge this gap by examining students' respect for teachers within the context of Islamic Education at SMA Surya Buana Malang. Specifically, this study explores using hypnoteaching methods to enhance students' understanding and practice of tawadhu' towards their educators. Employing a qualitative approach, this research involved students from class X at SMA Surya Buana Malang. Data collection methods included interviews and questionnaire surveys to assess the development of Students’ Humility traits following the implementation of hypnoteaching. The findings indicate that integrating hypnoteaching into instructional practices positively impacts the cultivation of students' humility. Students showed increased motivation to practice tawadhu’ daily and a deeper understanding of its importance. Additionally, they reported improved attitudes towards others, displaying greater humility and a willingness to learn from their peers.